Irrigation and Household Water Test and Interpretation - Rao Mylavarapu (EDIS)
Analytical tests for samples of water from sources, usually wells, intended for irrigation and/or household usage are offered through the University of Florida/IFAS Extension Soil Testing Laboratory (ESTL) in Gainesville. The tests offered only help diagnose potential problems in the pipelines and plumbing. The ESTL does not test for suitability of the water for human consumption. Test for bacteria and other contaminants with regards to human consumption may be available from your County Health Department or from selected commercial laboratories. This document is SL219, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date October 2004.